Gatifloxacin Loaded Nano Lipid Carriers for the Management of Bacterial Conjunctivitis - Poorva H. Joshi; Ahmed Adel Ali Youssef; Mihir Ghonge; Corinne Varner; Siddharth Tripathi; Narendar Dudhipala; Soumyajit Majumdar (MDPI AG, 2023)
Bacterial conjunctivitis (BC) entails inflammation of the ocular mucous membrane. Early effective treatment of BC can prevent the spread of the infection to the intraocular tissues, which could lead to bacterial endophthalmitis or serious visual disability. In 2003, gatifloxacin (GTX) eyedrops were introduced as a new broad-spectrum fluoroquinolone to treat BC. Subsequently, GTX use was extended to other ocular bacterial infections. However, due to precorneal loss and poor ocular bioavailability, frequent administration of the commercial eyedrops is necessary, leading to poor patient compliance. Thus, the goal of the current investigation was to formulate GTX in a lipid-based drug delivery system to overcome the challenges with the existing marketed eyedrops and, thus, improve the management of bacterial conjunctivitis. GTX-NLCs and SLNs were formulated with a hot homogenization-probe sonication method. The lead GTX-NLC formulation was characterized and assessed for in vitro drug release, antimicrobial efficacy (against methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa), and ex vivo permeation. The lead formulation exhibited desired physicochemical characteristics, an extended release of GTX over a 12 h period, and was stable over three months at the three storage conditions (refrigerated, room temperature, and accelerated). The transcorneal flux and permeability of GTX from the GTX-NLC formulation were 5.5- and 6.0-fold higher in comparison to the commercial eyedrops and exhibited a similar in vitro antibacterial activity. Therefore, GTX-NLCs could serve as an alternative drug delivery platform to improve treatment outcomes in BC.